Dynamics of Gold Prices in Indonesia; A Short-Term and Long-Term Estimation Approach - Hasanudin; Romi Suradi; Eko Supriyanto; Angga Permadi (Fakultas Ekonomi dan Bisnis Islam UIN Alauddin Makassar, 2022)
The issue of reinstating the role of gold in the financial system which was no longer supported by gold since 1971 resurfaced. The role of money based on gold is an attempt to create a stable and fair monetary system. This study tries to see the effect of GDP growth, inflation, dollar exchange rate, and the composite stock price index on gold prices in Indonesia. The analysis technique used is ARDL (Autoregressive Distributed Lag). The results showed that the variables of GDP, inflation, dollar exchange rate, and JCI in the long term ARDL had no significant effect. In the short term for 1991Q1 – 2019Q3 data, the dollar exchange rate variable has a positive effect on gold prices. Meanwhile, in the short term, data for 1999Q2 – 2019Q3 GDP and the dollar exchange rate have a negative effect on gold prices. This shows that in the short term gold can be used as safe storage when the country's economic growth is unstable. The implication of this research is the government and other related parties to continue to increase economic growth and gross domestic product, besides the importance of maintaining economic and political stability in order to ensure the sustainability of the economy in Indonesia, so that inflation can be more controlled and the composite stock price index will improve in the future.